Development of a human antibody cocktail that deploys multiple functions to confer pan-ebolavirus protection - Wec, Anna Z. (Cell Host Microbe, 2019)
Passive administration of monoclonal antibodies (mAbs) is a promising therapeutic approach for Ebola virus disease (EVD). However, all mAbs and mAb cocktails that have entered clinical development are specific for a single member of the Ebolavirus genus, Ebola virus (EBOV), and ineffective against outbreak-causing Bundibugyo virus (BDBV) and Sudan virus (SUDV). Here, we advance MBP134, a cocktail of two broadly neutralizing human mAbs, ADI-15878 from an EVD survivor and ADI-23774 from the same survivor but specificity-matured for SUDV GP binding affinity, as a candidate pan-ebolavirus therapeutic. MBP134 potently neutralized all ebolaviruses and demonstrated greater protective efficacy than ADI-15878 alone in EBOV-challenged guinea pigs. A second-generation cocktail, MBP134(AF), engineered to effectively harness natural killer (NK) cells afforded additional improvement relative to its precursor in protective efficacy against EBOV and SUDV in guinea pigs. MBP134(AF) is an optimized mAb cocktail suitable for evaluation as a pan-ebolavirus therapeutic in nonhuman primates.